Sustainable Land Management for Mitigating Desertification in Nimroz Province - Qaderi, Abdul Rawof (Journal of Natural Sciences – Kabul University, 2026)
Nimroz Province, located in southwestern Afghanistan, is exposed to desertification due to its arid and semi-arid climate. Reduced rainfall, rising air temperatures, overgrazing, and unsustainable use of natural resources are considered the main factors contributing to the degradation of vegetation cover in this province. This study was conducted to assess the status of desertification in Nimroz and to identify the factors influencing it. For this purpose, changes in land cover for the years 2000, 2010, and 2020, as well as trends in rainfall, humidity, and air temperature over a decade, were analyzed to determine the role of climatic indicators in accelerating desertification. The results indicate that the significant decline in vegetation cover and the increase in barren lands are directly associated with decreased rainfall and rising air temperatures. Finally, key strategies for controlling desertification and achieving sustainable land management are proposed.